The effect of the lamb sex and length of lactation on growth and carcass characteristics and meat shear force in corriedale lambs slaughtered at 5 month of age - Garibotto, G.; Bianchi, G.; Franco, J.; Bentancur, O.; Perrier, J.; González, J. (Agrociencia Uruguay, 2003)
The effect of the lamb sex (ram: lr, wether: lw, cryptorchid: lcand female: lf) and length of lactation (weaned lambs 82 ± 6.8 days and unweaned lambs: 163 ± 7.0 days) on growth, carcass and meat characteristics of 72 Corridale lambs slaughtered at a fixed date with 163 ± 7.0 days of age and 33.0 ± 4.9 kg of live weight were studied. Growth rate from birth to slaughterwas affected by length of lactation (181 vs 158 g/day, unweaned and weaned lambs, respectively; p=0.0006), determining weights to slaughter singificantly higher is not weaned lambs opposite to the weaned ones (34.8 vs 31.8 kg, respectively; p=0.0009) and better body condition (3.4 vs 3.0, respectively; p=0.004). The length of lactation for sex of the lamb interaction was significant (p£0.05) only for carcass weight. Carcass of unweaned lambs were classified with better conformation note that weaned lambs (3.54 vs 3.36, 1-4 scale, respectively; p=0.02). Lamb sex only affected slaughter weight (35.6, 33.4, 32.4 and32.0 kg, lw, lc, lr and if, respectively; p=0.01) and GR values (6.2, 6.4, 6.7 y 8.3 mm, lr, lw, lc and lf, respectively; p£0.05). The cuts from the break-down of carcass and meat color and texture were not affected (p>0.05) for any treatment.